The Melody book : 300 selections from the world of music for autoharp, guitar, piano, recorder, and voice - Hackett, Patricia, 1932-; Holub, Florence (Prentice Hall, 1992)
Includes folk music from around the world, jazz, popular tunes, children's songs, and symphonic themes, with chord charts and strumming patterns.